Molecular Epidemiology, Seroprevalance, Serum BiochemicalAlterations and In Silico Analysis of African Swine FeverVirus in Karnataka - Nagaraju, Praveena Hullahalli; Shankar, Byadarahalli Puttaswamy; Doreswamy, Ramesh; Puttamallappa, Ravikumar; Parameshwarappa, Satheesha Settihally; Sheela, Purushottam (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
African swine fever (ASF) is a highly contagious and haemorrhagic disease affecting swine, characterized by a significant morbidity and mortality rate. Recognized as a crucial swine disease by the World Organization for Animal Health (WOAH), it is classified as a Transboundary Animal Disease. Comprehensive understanding of ASF necessitates studying its pathology, pathogenesis, and molecular characterization of individual ASF virus isolates. This study aimed to investigate the seroprevalence of ASF in southern regions of Karnataka and examine the associated pathomorphological changes in isolates from this area. ASF outbreaks occurred in Karnataka between 2022 and 2024, resulting in substantial losses for farmers. Indirect ELISA testing revealed that 14.58% of serum samples tested positive for ASFV antibodies. ASFV confirmation was achieved through PCR targeting the p72 gene, identifying 11 positive cases. Two strains of ASF were isolated from Karnataka, with their pathomorphological features analysed. Phylogenetic analysis of the two Karnataka isolates indicated similarity to the West Bengal isolate.
Keywords: African swine fever; Biochemical parameters; In-silico analysis; Molecular Epidemiology,